PEMBERDAYAAN MASYARAKAT MELALUI MODEL PERILAKU BERBASIS TRANSCULTURAL CARE PADA PENCEGAHAN DAN PENANGANAN BALITA STUNTING DAN CARIES - Sukini Sukini; Yayuk Fathonah; Suyanta Suyanta; Angga Sugiarto (Journal of Midwifery in Community (JMC), 2024)
Community empowerment is an effective approach in preventing and addressing health issues in children, such as stunting and dental caries. The transcultural care-based behavioral model offers a holistic approach by incorporating local cultural values into health interventions. This study aims to explore and implement a community empowerment model based on transcultural care to prevent stunting and dental caries in young children. The method used involves active community participation in health education, awareness programs, and initiatives that engage cultural leaders and healthcare professionals. The results show that a culturally sensitive approach increases community acceptance and participation in health programs, significantly contributing to the reduction of stunting and dental caries in children. In conclusion, the transcultural care model can be an effective strategy for empowering communities to achieve better child health, particularly in the context of preventing and managing stunting and dental caries.